2022
DOI: 10.1177/14680874221133223
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of diesel engine performance and emission characteristics with cerium oxide nanoparticles mixed waste cooking oil biodiesel blends

Abstract: The study investigates the performance and emission characteristics of a four-stroke, single-cylinder, and direct injection diesel engine with variable compression ratio using nanoparticles blended biofuel. The cerium Oxide (CeO2) nanoparticles have been blended in corresponding ratios with waste cooking oil (WCO) biodiesel. Further, response surface methodology (RSM) based Box-Behnken design (BBD) approach was used to evaluate engine performance parameters such as brake specific fuel consumption (BSFC), brake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…They found that adding nanoparticles into biodiesel decreased the HC and NO X emissions when compared with biodiesel without nano-additives. It was stated that blends of WCO and CeO 2 nanoparticles enhanced the BTE by 36.62% and reduced the hazardous emissions of CO, NO X , and CO 2 by 0.0192%, 168 ppm, and 1.132%, respectively [20].…”
Section: Introductionmentioning
confidence: 99%
“…They found that adding nanoparticles into biodiesel decreased the HC and NO X emissions when compared with biodiesel without nano-additives. It was stated that blends of WCO and CeO 2 nanoparticles enhanced the BTE by 36.62% and reduced the hazardous emissions of CO, NO X , and CO 2 by 0.0192%, 168 ppm, and 1.132%, respectively [20].…”
Section: Introductionmentioning
confidence: 99%
“…The second article by Bidir et al 4 compares the effects of using nanoparticles in ternary fuel blends on combustion, emissions, and performance characteristics of diesel engines. The next article by Lakhera et al 5 deals with efforts to optimize of performance and emission characteristics of diesel engines fueled with cerium oxide nanoparticles mixed in diesel. Ahmed et al 6 execute an experimental investigation of the performance and emission characteristics of CI Engines running on diesel/biodiesel blends mixed with nanoparticle additives.…”
mentioning
confidence: 99%